PENGARUH LABEL HALAL, ELECTRONIC WORD OF MOUTH DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK HALAL - Kakanita Ari Puspitasari; Titik Desi Harsoyo (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to examine the influence of Halal Labels, Electronic Word of Mouth and Product Attributes on Purchasing Decisions of Halal Cosmetic Products. This type of research is classified as quantitative research. The independent variables in this study consisted of Halal Labels, Electronic Word of Mouth and Product Attributes. While the dependent variable is the Purchase Decision. The respondents used in this study were 124 respondents who had purchased and used halal cosmetic products, namely wardah. All question items used in this study proved to be valid and reliable after being tested for validity and reliability tests. The data analysis tool used in this study uses IBM SPSS Statistics 21. Data analysis in this study uses Multiple Regression Analysis. In the classical assumption test, this research is normally distributed, the regression model does not occur multicollinearity and does not occur heteroscedasticity. The results of this study indicate that the Halal Label has a positive and significant effect on Purchase Decisions, Electronic Word of Mouth has a positive and significant effect on Purchase Decisions, Product Attributes have a positive and significant effect on Purchase Decisions. Based on the results of testing the data, all hypotheses in this study are supported.